Composition and antifungal mechanism of essential oil from Chrysanthemum morifolium cv. Fubaiju. (December 2021) - Zhan, Jianfeng; He, Feng; Cai, Huimin; Wu, Meichan; Xiao, Yunli; Xiang, Fu; Yang, Ying; Ye, Chen; Wang, Shuzheng; Li, Shiming
Graphical abstract: Highlights: Components of Chrysanthemum morifolium cv. Fubaiju essential oil (CMF-EO) were characterized. CMF-EO showed excellent antifungal activities against six common fungus. Antifungal targets were cell membrane, mitochondrial membrane, and DNA. Multiple antifungal mechanisms make fungi difficult to develop drug resistance. Abstract: Chrysanthemum morifolium cv. Fubaiju (CMF) has been used as a dietary herb in East Asia for centuries. The chemical composition and antifungal activity of CMF essential oil (CMF-EO) were investigated in this study. We have found that CMF-EO was a light-yellow, transparent liquid (0.61% yield, w/w) and majorly contain 31 volatile components with a total of 98.41% determined by GS and GC/MS. Camphor was the major compound (16.87%), followed by 1, 8-cineole (10.62%), β -curcumene (9.51%), bornyl acetate (7.43%), α -zingiberene (6.97%), β-elemene (6.47%), α -bisabolol (4.74%), borneol (4.24%) and eugenol (4.23%). In addition, contents with more than 2% of the total CMF-EO were 1-caryophyllene (3.92%), chrysanthenyl acetate (3.29%), caryophyllene oxide (2.28%), and chamazulene (2.23%). Six fungal strains were used to study the antifungal activities and mechanisms of CMF-EO using fluorescence probe–membrane integrity assay, analysis of cytoplasmic membrane permeability, electron microscopy, monitoring of the effect of the mitochondrial membrane potential and DNA binding assay. CMF-EO effectively inhibited the growth of C. albicans, C. glabrata, C. tropicalis, S. cerevisiae, D. hansenii, and Z. parabailii with minimum inhibition concentrations of 31.25, 31.25, 62.5, 31.25, 15.625, and 15.625 μg/mL, respectively, and minimum fungicidal concentrations of 62.5, 125.0, 125.0, 62.5, 31.25, and 62.5 μg/mL, respectively. The elucidated antifungal mechanisms of CMF-EO included the destruction of cytoplasmic membrane and the damage of mitochondria and DNA. The multiple antifungal mechanisms made it difficult for fungi to develop drug resistance, and this finding might shed new light on the development of new fungal agents.